KOMODIFIKASI PADA TARI SRIMPI MERAK KESIMPIR KARYA HAMENGKUBUWANA KE VII - Sawitri, Sawitri; Marmoah, Sri; Nurhasanah, Farida; Wicaksana, Muhlis Fajar (Universitas Muria Kudus, 2023)
The aim of this research is to determine the sacredness of the Srimpi Merak Kesimpir dance and how to preserve it using qualitative descriptive methods. The Peacock Kesimpir Dance by Hamengkubuwana VII is a dance that was sacred at the beginning of creation. A king's work is a talisman or heirloom that is always looked after and maintained for the preservation of the sacred dance work.The research method used is qualitative descriptive using interviews, photo documents, reference books, videos, online magazines, e-books and other very in-depth data for cultural experts.The results of the research found that commodification in the peacock kesimpir dance, which was previously only performed in the palace environment, is now being performed outside the palace to function as a cultural performance. Clothes, floor patterns and even jewelry are all made better and more attractive. In terms of sacredness, it is certainly reduced, but in terms of preservation, it is one solution to be sustainable. Every work of art will experience development, even if it is a work from hamengkubuwana to VII. The king's masterpieces are inseparable from being in line with the times.